MC03g0810, an Important Candidate Gene Controlling Black Seed Coat Color in Bitter Gourd (Momordica spp.) - Zhong, Jian; Cheng, Jiaowen; Cui, Junjie; Hu, Fang; Dong, Jichi; Liu, Jia; Zou, Yichao; Hu, Kailin (Frontiers in Plant Science, 2022)
Seed coat color is one of the most intuitive phenotypes in bitter gourd (Momordica spp.). Although the inheritance of seed coat color has been reported, the gene responsible for seed coat color is still unknown. This study used two sets of parents, representing respectively the intersubspecific and intraspecific materials of bitter gourd, and their respective F1 and F2 progenies for genetic analysis and primary mapping of seed coat color. A large F2:3 population comprising 2975 seedlings from intraspecific hybridization was used to fine map the seed coat color gene. The results inferred that a single gene, named McSC1, controlled seed coat color and that the black color was dominant over yellow. The McSC1 locus was mapped to a region with a physical length of ~7.8 Mb and 42.7 kb on pseudochromosome 3 via bulked segregant analysis with whole-genome resequencing (BSA-seq) and linkage analysis, respectively. Subsequently, the McSC1 locus was further fine mapped to a 13.2 kb region containing only one candidate gene, MC03g0810, encoding a polyphenol oxidase (PPO). Additionally, the variations of MC03g0810 in the 89 bitter gourd germplasms showed a complete correlation with seed coat color. Expression and PPO activity analyses showed a positive correlation between expression level of MC03g0810 and its product PPO and seed coat color. Therefore, MC03g0810 was proposed as the causal gene of McSC1. Our results provide an important reference for molecular marker-assisted breeding based on seed coat color and uncover molecular mechanisms of seed coat color formation in bitter gourd.